Efektivitas Pembelajaran Triase Berbasis Simulasi terhadap Kompetensi Triase Mahasiswa Keperawatan pada Prodi D-III Keperawatan Aceh Tenggara Poltekkes Kemenkes Aceh - Devi Susanti (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Emergency services require timely access and appropriate competence in ensuring patient safety. Triage competency supports nursing task performance and nurse self-efficacy in the emergency department. However, the triage competence of nurses is still low in terms of the lack of knowledge of triage nurses, negative nurse practices, and attitudes. Clinical practice education programs must be developed to improve clinical reasoning competencies in order to improve the triage competence of nursing students. Simulation-based triage learning is a teaching method by designing triage concepts, discussing cases, and simulating triage actions into video media. The use of video in triage learning includes creative and innovative methods in increasing learning motivation. This study aims to analyze the effectiveness of simulation-based triage learning on the triage competence of nursing students in the D-III Nursing Study Program, Poltekkes Kemenkes Aceh. The research design is a quasi-experimental study with a pre and post-test approach without control. The population in this study were all students of the Southeast Aceh D-III Nursing study program, the Aceh Ministry of Health Polytechnic, totaling 76 people. Sampling using the total sampling technique must meet the inclusion criteria. The results of data analysis using the Wilcoxon test found that the average triage competence of nursing students before learning triage based on simulation was 118.43. The mean triage competence of nursing students after triage learning based on simulation was 162.97. There was a significant effect of nursing management e-learning collaboration on increasing the competence of nursing students. There is a significant effect of simulation-based triage competency learning on the improvement of nursing students' triage competence. Based on the results of this study, it is suggested to educators be able to design nursing action videos in applying simulation-based learning methods to achieve student triage competencies. Keywords: Competency, Nursing, Triage, Simulation. ABSTRAK Pelayanan gawat darurat membutuhkan akses tepat waktu dan kompetensi yang sesuai dalam menjamin keselamatan pasien. Kompetensi triase mendukung kinerja tugas keperawatan dan self-efficacy perawat di bagian gawat darurat. Namun, kompetensi triase perawat masih rendah dari aspek pengetahuan triase perawat yang kurang, praktik dan sikap perawat negatif. Program pendidikan praktek klinis harus dikembangkan untuk meningkatkan kompetensi penalaran klinis dalam rangka meningkatan kompetensi triase mahasiswa perawat. Pembelajaran triase berbasis simulasi merupakan metode pengajaran dengan mendesain konsep triase, pembahasan kasus dan simulasi tindakan tiase ke dalam media video. Penggunaan video dalam pembelajaran triase termasuk metode yang bersifat kreatif dan inovatif dalam meningkatkan motivasi pembelajaran. Penelitian ini bertujuan menganalisis efektivitas pembelajaran triase berbasis simulasi terhadap kompetensi triase mahasiswa keperawatan pada Program Studi D-III Keperawatan Poltekkes Kemenkes Aceh. Desain penelitian ini adalah penelitian quasi experimental dengan pendekatan pre and post test without control. Populasi dalam penelitian ini adalah semua mahasiswa program studi D-III Keperawatan Aceh Tenggara, Poltekkes Kemenkes Aceh yang berjumlah 76 orang. Pengambilan sampel menggunakan teknik total sampling dan harus memenuhi kriteria inklusi. Hasil analisis data dengan menggunakan uji wilcoxon didapatkan bahwa rerata kompetensi triase mahasiswa keperawatan sebelum pembelajaran triase berbasis simulasi adalah 118,43. Rerata kompetensi triase mahasiswa keperawatan setelah pembelajaran triase berbasis simulasi yaitu 162,97. Terdapat pengaruh signifikan kolaborasi e-learning manajemen keperawatan terhadap peningkatan kompetensi mahasiswa keperawatan. Terdapat pengaruh yang signifikan pembelajaran kompetensi triase berbasis simulasi terhadap peningkatan kompetensi triase mahasiswa keperawatan. Berdasarkan hasil penelitian tersebut, maka disarankan kepada pendidik agar dapat mendesain video tindakan keperawatan dalam menerapkan metode pembelajaran berbasis simulasi untuk pencapaian kompetensi triase mahasiswa. Kata Kunci: Kompetensi, Keperawatan, Triase, Simulasi